2017
DOI: 10.3389/fphar.2017.00301
|View full text |Cite|
|
Sign up to set email alerts
|

An Antifungal Mechanism of Protolichesterinic Acid from the Lichen Usnea albopunctata Lies in the Accumulation of Intracellular ROS and Mitochondria-Mediated Cell Death Due to Apoptosis in Candida tropicalis

Abstract: Candida species causes superficial and life-threatening systemic infections and are difficult to treat due to the resistance of these organism to various clinically used drugs. Protolichesterinic acid is a well-known lichen compound. Although the antibacterial activity of protolichesterinic acid has been reported earlier, the antifungal property and its mechanism of action are still largely unidentified. The goal of the present investigation is to explore the anticandidal activity and mechanism of action of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Mitochondria play an essential role in the life cycle of cells, including ATP synthesis, calcium mobilization, and apoptosis-programmed cell death . Thus, similar to the plasma membrane, the mitochondria are another potential antifungal target. Furthermore, several previous studies have demonstrated that mitochondria-mediated apoptosis occurs not only in multicellular organisms but also in single-cell organisms such as fungi, , and the antifungal mechanisms associated with the form of apoptosis triggered by mitochondrial dysfunction and disruption have been proposed. In this study, it was found that PS externalization as an early marker of apoptosis occurred in the A. flavus spores inhibited by ( E )-2-hexenal. However, systematic studies on the apoptosis of A. flavus spores induced by ( E )-2-hexenal need to be further investigated, including mitochondrial membrane potential, cytochrome c release, intracellular Ca 2+ levels, activation of metacaspases, and DNA damage.…”
Section: Discussionmentioning
confidence: 65%
“…Mitochondria play an essential role in the life cycle of cells, including ATP synthesis, calcium mobilization, and apoptosis-programmed cell death . Thus, similar to the plasma membrane, the mitochondria are another potential antifungal target. Furthermore, several previous studies have demonstrated that mitochondria-mediated apoptosis occurs not only in multicellular organisms but also in single-cell organisms such as fungi, , and the antifungal mechanisms associated with the form of apoptosis triggered by mitochondrial dysfunction and disruption have been proposed. In this study, it was found that PS externalization as an early marker of apoptosis occurred in the A. flavus spores inhibited by ( E )-2-hexenal. However, systematic studies on the apoptosis of A. flavus spores induced by ( E )-2-hexenal need to be further investigated, including mitochondrial membrane potential, cytochrome c release, intracellular Ca 2+ levels, activation of metacaspases, and DNA damage.…”
Section: Discussionmentioning
confidence: 65%
“…Kumar et al (2017) extracted protolichesterinic acid from Usnea albopunctata and studied its antifungal effect against four Candida species, including C. albicans and C. parapsilosis; the diameters of inhibition zones were 21 mm and 22 mm, respectively [ 78 ]. Our results also showed that the antifungal activity of usnic acid was higher against C. parapsilosis (20 mm) than against C. albicans (10 mm).…”
Section: Discussionmentioning
confidence: 99%